Análise funcional das proteínas desacopladas mitocondriais de plantas utilizando RNA-seq e mutantes de inserção - Laitz, Alessandra Vasconcellos Nunes [UNESP] (2014)
Mitochondrial inner membrane uncoupling proteins (UCP) dissipate the proton electrochemical gradient established by the respiratory chain, thus affecting the yield of ATP synthesis. These proteins play a role in maintaining mitochondrial function and their importance as cellular oxidative stress tolerance component has been demonstrated in several studies performed in vitro and in vivo. In this study, the functional role of plant UCPs was investigated. In a first approach, a transcriptomic analysis of tobacco plants overexpressing the AtUCP1 gene of Arabidopsis thaliana was performed using RNA-seq analysis. The RNA-sequencing generated over a million of reads with 150 base pair on average for each library. From these reads, a set of approximately 34,000 contigs was obtained. A total of 816 differentially expressed genes between transgenic lines and wild-type control was identified. Amongst them, 239 were up-regulated (p≤0,001) and 577 were down-regulated (p≤0,001). In parallel, a gene expression analysis was performed using Arabidopsis insertion mutants for the AtUCP1-3 genes, two of them (atucp2 and atucp3) being characterized in this study. The main purpose was to verify the functionality and the existence of redundancy between the target genes. According to the obtained results, a compensatory expression was observed only in the atucp3 background, in which the AtUCP1 and AtUCP2 genes were induced both in normal physiological conditions and under salt and osmotic stresses